2018
DOI: 10.1089/end.2018.0291
|View full text |Cite
|
Sign up to set email alerts
|

“Stoneless” or Negative Ureteroscopy: A Reality in the Endourologic Routine or Avoidable Source of Frustration? Estimating the Risk Factors for a Negative Ureteroscopy

Abstract: Female gender, a nonradio-opaque stone at KUB, and a smaller stone surface were statistically significantly different in the Negative-URS population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 13 publications
4
19
1
Order By: Relevance
“…1). Eight full-text articles were obtained and finally 4 studies (1336 patients) were selected for our review [17][18][19][20]. These studies were published from 2011 to 2018, covering URS procedures carried out between 2003 and 2015.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Eight full-text articles were obtained and finally 4 studies (1336 patients) were selected for our review [17][18][19][20]. These studies were published from 2011 to 2018, covering URS procedures carried out between 2003 and 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Kreshover et al, however, did not find sex to be a significant predictive factor for negative URS [20]. Katafigiotis and colleagues also found that non-radiopaque stones significantly predicted negative URS (OR 11.11; CI 2.51, 49.20; p = 0.002) [17]. They used a multivariate model which combined stone length, surface area, volume, and width on CT scan and found that smaller size significantly predicted negative URS (AUC 0.95; CI 0.92-0.97; p < 0.0001).…”
Section: Negative Urs Rate and Predictive Factorsmentioning
confidence: 94%
See 3 more Smart Citations